Innovative Approach to Reading Skill Development: Jigsaw Strategy and Crossword Puzzle Media - Hasibuan, Renni; Laily Fitriani (Journal of Arabic Language Learning and Teaching (JALLT), 2023)
This article aims to describe application of jigsaw learning strategy and crossword puzzle in Maharah qiraah learning, which includes three aspects: 1) planning, 2) implementation, and 3) evaluation. This research uses a qualitative approach with descriptive method. Data collection technique used observation, interviews and documentation. The research results are: 1) planning Maharah qiraah learning by applying jigsaw strategy and crossword puzzle media in form of preparing a lesson plan and preparing crossword puzzle questions related to social text material. 2) implementation of Maharah qiraah learning by applying jigsaw model and crossword puzzle media in form of opening activities namely class conditioning and delivery of learning objectives, and core activity is studying qiraah material with jigsaw model with the steps: instructing jigsaw model, forming original group, continuing to form expert group, after which each expert group presented the results of discussion related to paragraphs that had been discussed, evaluation from lecturer. 3) evaluation is carried out by distributing crossword puzzle worksheets to each student and then they are welcome to work on each one. The implications of this research can help improve the quality of Maharah qiraah learning and provide a more innovative and interesting approach for students in understanding Arabic texts.